The impact of monetary, accessibility, security towards religious tourism intention among Muslims youth - Shazli, Wan Nuriffa Azima Wan; Saad, Mazni (2019)
Religious tourism is one of the types of tourism that becomes a phenomenon in the current era. Religious tourism involved going to a place that gives self-conscious project f spiritual betterment. In the context of religious tourist, as it received a huge number of tourists annually, wellness of religious traveller is an important matter to be considered. This research is to measure Malaysia's Muslims youth religious tourism intention and the impact of accessibility, monetary and security. This study focusing on three objectives which are: 1) to identify the current intention level of Muslims youth towards religious tourism, 2) to investigate impact of monetary, accessibility, security towards religious tourism intention among Muslim youth in Malaysia, and 3) to examine the most influential factor that contributes towards Muslims youth intention in religious tourism. This study is quantitative in nature. A total of 52 respondents of Muslims youth that ages from 5 until 30 years old have participated in this research. The data was analyzed by using IBM SPSS version 21 through several analyses such as descriptive analysis, frequency analysis, reliability analysis, Pearson correlation analysis and multiple regression analysis. The outcomes of this study show the most influential factor that contributes towards Muslims youth intention in religious tourism and the relationship analysis show that the monetary, accessibility and security has a significant relationship between religious tourism intention among Muslims youth while the most influential factor is the monetary impact towards religious tourism intention among Muslims youth. The first major practical contribution of the study is that it has a significant contribution to the Hajj and Umrah tour organizer as they can improve on facilities or services demanded by Muslims youth to perform Hajj.